Ayushman Bharat: Service Adoption Challenges in Universal Healthcare System. (April 2021) - Pandey, Neeraj; Jha, Sumi; Rai, Vaibhav
The Ayushman Bharat, the universal healthcare scheme in India, faced service adoption challenges after its launch in 2018. It was an enigma for the top management in Ayushman Bharat regarding slower service adoption of a free mass healthcare coverage scheme by the target population. The case focuses on the service adoption challenges from patient and physician perspectives while implementing a universal healthcare system. It provides insights to policymakers, physicians, service operations managers, and healthcare administrators regarding managing the universal healthcare system's implementation challenges in a developing country context. Research questions/Objective: This study aims to understand service adoption challenges in a universal healthcare system setting. The study explores the following research questions: How is service adoption theory applied in a universal health coverage program? What should be the integrated marketing communication plan to improve the awareness about a universal healthcare program? Links to theory: The study uses service adoption theory. It analyzes service adoption challenges for the universal healthcare system in India called Ayushman Bharat. It also uses literature on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Phenomenon studied: The case study uses pan India patient and physician data to explore service adoption issues in Ayushman Bharat - a universal healthcare scheme in India. Case context: The primary data collected through the field (hospital) visits and interaction with patients and physicians of Ayushman Bharat form the basis of this case study. Findings: The study emphasizes on performance expectancy, ease in availing of the service, positive social influence, and facilitating conditions for service delivery of Ayushman Bharat. The Ayushman Bharat scheme's performance expectancy means how being a healthy individual would contribute to better performance at the workplace. The effort expectancy is the level of ease an eligible Ayushman Bharat scheme can avail the service at the empanelled hospital. The social acceptance of the Ayushman Bharat scheme by friends, peers, and people in the vicinity would create a positive social influence. The facilitating conditions in the Ayushman Bharat scheme are the government's capacity to provide organizational and technological infrastructure to support this universal healthcare program. Discussions: The use of service adoption theory and the UTAUT model to enhance the adoption of the universal healthcare system in India have been discussed in the case study.